Android-Based Application (SiBen) to Improving Readiness Towards Hurricane In Lubuklinggau 2020 - Susmini; Sapondra Wijaya; Wahyu Dwi Ari Wibowo; Jhon Feri (Alta Dharma Publisher, 2021)
One of disaster-prone country in the world is Indonesia. Communities have to ready toward the disasters. To strengthen the community's readiness in dealing with disasters, knowledge must be increased. Better educational methods are needed to convey material, one of which is by utilizing technology. The purpose of this research was to build and test the SiBen application’s effectiveness as a media for disaster education to improve the readiness toward hurricane in Lubuklinggau community. The method was Research and Development (R&D) with experimental tests, Pre and post-test were applied in this study. Fourty people were given three meetings within 2 weeks. As the result, the participants have shown progression of readiness (t = 3.168, p < 0.002). The findings indicated that the SiBen Application was effective to improve the readiness of community toward hurricane.